Early adolescent gender diversity and mental health in the Adolescent Brain Cognitive Development study. (28th May 2020) - Potter, Alexandra; Dube, Sarahjane; Allgaier, Nicholas; Loso, Hannah; Ivanova, Masha; Barrios, Lisa C.; Bookheimer, Susan; Chaarani, Bader; Dumas, Julie; Feldstein‐Ewing, Sarah; Freedman, Edward G.; Garavan, Hugh; et al.
Abstract : Background: There are known associations between mental health symptoms and transgender identity among adults. Whether this relationship extends to early adolescents and to gender domains other than identity is unclear. This study measured dimensions of gender in a large, diverse, sample of youth, and examined associations between diverse gender experiences and mental health. Methods: The ABCD study is an ongoing, longitudinal, US cohort study. Baseline data (release 2.0) include 11, 873 youth age 9/10 (48% female); and the 4, 951 1‐year follow‐up visits (age 10/11; 48% female) completed prior to data release. A novel gender survey at the 1‐year visit assessed felt‐gender, gender noncontentedness, and gender nonconformity using a 5‐point scale. Mental health measures included youth‐ and parent‐reports. Results: Roughly half a percent of 9/10‐year‐olds ( n = 58) responded 'yes' or 'maybe' when asked, 'Are you transgender' at baseline. Recurrent thoughts of death were more prevalent among these youth compared to the rest of the cohort (19.6% vs. 6.4%, χ 2 = 16.0, p < .001). At the 1‐year visit, when asked about the three dimensions of gender on a 5‐point scale, 33.2% ( n = 1, 605) provided responses that were not exclusively and totally aligned with one gender. Significant relationships were observed between mental health symptoms and gender diversity for all dimensions assessed. Conclusions: Similar to adult studies, early adolescents identifying as transgender reported increased mental health symptoms. Results also point to considerable diversity in other dimensions of gender (felt‐gender, gender noncontentedness, gender nonconformity) among 10/11‐year‐olds, and find this diversity to be related to critical mental health symptoms. These findings add to our limited understanding of the relationship between dimensions of gender and wellness for youth.